Celebrating Arthur Darby Nock: choice, change, and conversion - Calhoun, Robert Matthew; Kelhoffer, James A.; Rothschild, Clare K.; Nock, Arthur Darby (Wissenschaftliche Untersuchungen zum Neuen Testament, 2021)
Cover -- Title -- Preface and Acknowledgments -- Table of Contents -- List of Abbreviations -- Clare K. Rothschild - Introduction: Conversion Since Nock -- Part One: Responses to Nock's Conversion -- Jan N. Bremmer - Notes on Arthur Darby Nock's Ideas of Ancient Religion and the Mysteries in His Conversion -- John J. Collins - Nock's Typology of Religion -- Carl R. Holladay - A. D. Nock's Conversion: Some Glosses -- John S. Kloppenborg - Rethinking Nock's Conversion -- Paula Fredriksen - "Conversion" as "Sea Change": Re-thinking A. D. Nock's Conversion -- L. L. Welborn - Nock on the Exclusiveness of Conversion to Christianity: A Re-evaluation with Reference to Evidence from Roman Corinth -- Michael B. Cover - The Conversion and Return of Simon Peter (Luke 22:31-32) -- Harold W. Attridge - Celebration of Arthur Darby Nock -- Christopher Mount - Conversion and the Success of Christianity in the Roman Empire -- James A. Kelhoffer - Do ΜΕΤΑΝΟΕΩ and ΜΕΤΑΝΟΙΑ in Second Clement Signify "Repentence" or a Change in Mindset Tantamount to Conversion? -- Carl Johan Berglund - Miracles, Determination, and Loyalty: The Concept of Conversion in the Acts of John -- Meira Z. Kensky - "Thus a Teacher Must Be": Pedagogical Formation in John Chrysostom's Homilies on 1 and 2 Timothy -- Andrew S. Jacobs - "Coloured by the Nature of Christianity": Nock's Invention of Religion and Ex-Jews in Late Antiquity -- Part Two: Beyond Conversion -- John T. Fitzgerald - Arthur Darby Nock and the Study of Sallustius -- Dylan M. Burns - The Hermetic Asclepius's Middle Platonist Teaching on Fate -- David Lincicum - In Search of Nock's Gifford Lectures: A Dossier of Sources -- Everett Ferguson - Afterword: Reminiscences of Arthur Darby Nock -- List of Contributors -- Bibliography -- Indices -- Index of References -- Index of Modern Authors.